EXPERIMENTAL STUDY OF FIBER REINFORCED COCONUT SHELL AGGREGATE CONCRETE WITH FLY ASH - Udayakumar, S.; kumar, K.Dinesh (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Solid wastes has increased many foldcausing disposal problems and environmentalpollution. It has become common sight to find largedumps of solid waste near every town and villagescausing air, land and water pollution. A productiveuse of large scale wastes such as fly ash, coconutshell, rice husks, furnace slag etc., has become amatter of importance, as there is considerable scopefor better management and disposal of the same.The waste materials considered in this work are flyash, coconut shell. The disposal method proposed isby partially using them in building elements such asreinforced concrete elements and plain concreteelements.In this study, the compressive strength ofconcrete cubes of size 150 mm was carried out. Thecement was replaced by 0% 10%, 20%, 30% of flyash and add 0%, 0.1%, 0.3% and 0.5% ofpolypropylene fibre. The optimum percentage wasfound. The crushed coconut shells as substitutes forconventional coarse aggregate in gradation of 50%and 100%. For these optimum percentages threebeams of 1700 X150 X100 mm were cast and tested.Extensive measurements such as materialproperties, deflection and ultimate load carryingcapacity of the beams were done in the study forcomparison.The experimental results shows that theultimate load carrying capacity of coconut shellaggregate beam with fly ash and polypropylenefibre were higher than the control beam. Thecompressive test and split tensile test indicate thatthe gain in strength depends on curing time andstrength increases gradually with the increase in flyash and fibre content. It is concluded that amaximum of 50% of coarse aggregate can bereplaced by coconut shell without any compromiseon strength properties. The aim behind this is to uselow cost material like coconut shell and thus takingclose to the concept of low cost housing.